Adsorption of elemental mercury vapors from synthetic exhaust combustion gas onto HGR carbon. (2nd July 2016) - Musmarra, D.; Karatza, D.; Lancia, A.; Prisciandaro, M.; Mazziotti di Celso, G.
ABSTRACT: An activated carbon commercially available named HGR, produced by Calgon-Carbon Group, was used to adsorbe metallic mercury. The work is part of a wider research activity by the same group focused on the removal of metallic and divalent mercury from combustion flue gas. With respect to previously published papers, this one is aimed at studying in depth thermodynamic equilibria of metallic mercury adsorption onto a commercial activated carbon. The innovativeness lies in the wider operative conditions explored (temperature and mercury concentrations) and in the evaluation of kinetic and thermodynamic data for a commercially available adsorbing material. In detail, experimental runs were carried out on a laboratory-scale plant, in which Hg° vapors were supplied in a nitrogen gas stream at different temperature and mercury concentration. The gas phase was flowed through a fixed bed of adsorbent material. Adsorbate loading curves for different Hg° concentrations together with adsorption isotherms were achieved as a function of temperature (120, 150, 200°C) and Hg° concentrations (1.0−7.0 mg/m 3 ). Experimental runs demonstrated satisfying results of the adsorption process, while Langmuir parameters were evaluated with gas–solid equilibrium data. Especially, they confirmed that adsorption capacity is a favored process in case of lower temperature and they showed that the adsorption heat was –20 kJ/mol. Furthermore, a numerical integration of differential equations that model the adsorption process was proposed. Scanning electron microscopy (SEM) investigation was an useful tool to investigate about fresh and saturated carbon areas. The comparison between them allowed identification of surface sites where mercury is adsorbed; these spots correspond to carbon areas where sulfur concentration is greater. Implications : Mercury compounds can cause severe harm to human health and to the ecosystem. There are a lot of sources that emit mercury species to the atmosphere; the main ones are exhaust gases from coal combustion and municipal solid waste incineration. Furthermore, certain CO2 capture processes, particularly oxyfuel combustion in a pulverized fuel coal-fired power station, produce a raw CO2 product containing several contaminants, mainly water vapor, oxygen, and nitrogen but also mercury, that have to be almost completely removed; otherwise these would represent a strong drawback to the success of the process.